Characterization and viability of the stromal vascular fraction from the Bichat fat ball associated with platelets-poor plasma - an option for aesthetic treatments (Research, Society and Development, 2021)
Bichectomy is a procedure that consists of removing the anterior portion of the Bichat adipose body (apBAB). The cell group obtained after processing through enzymatic digestion of this tissue is called the stromal vascular fraction (SVF). The nature of the cells that make up the SVF qualifies this product for a wide range of clinical applications, especially in procedures to stimulate renewal and repair, including the aesthetic purposes of rejuvenation in the face. However, the use of this living biological material is directly related to the proper handling and transport, from its collection, processing and return for clinical application. This study aimed to characterize the SVF obtained from apBAB, and also to verify whether autologous platelet-poor plasma (PPP) is efficient in maintaining cell viability, and can be a means of transport to its mediated clinical application. Three patients with indication for having a bichectomy participated in the study. Before removing the apBAB, venous blood collection was performed to obtain the PPP. The bilateral apBAB collected was sent to the Cell Processing Center Curityba Biotech and submitted to the protocol for separation of cells from its matrix. In the end, the SVF was divided into aliquots that were packed in syringes and in culture plates and evaluated for cell viability at times 0, 24 and 48 h. Cell viability and the characterization of cells present in SVF were evaluated by means of immunophenotyping by flow cytometry and by light microscopy. A sample was kept in a culture bottle until it reached 7x106 cells to prove the presence of mesenchymal stem cells capable of remaining in standard culture. The viability presented in the PPP medium remained constant and with a viability of 70% in up to 48 h. In addition, the sample analyzed by immunophenotyping confirmed the existence of: mesenchymal and hematopoietic stem cells, endothelial cells and T cells.